DEVELOPMENT OF A MOBILE WEB-BASED STOCK INFORMATION SYSTEM INTEGRATED WITH MARKETING STRATEGIES TO INCREASE SALES EFFECTIVENESS AT OPTIK HUSADA - Elisabet Yunaeti Anggraeni; Hesti Liana; M.Rayhan Juan Carlos (YHMM PUBLISHING, 2025)
This study aims to develop a web mobile-based inventory information system integrated with marketing strategies at Optik Husada. The main problem identified is the manual stock management system, which leads to data inconsistencies, delays in information retrieval, and low operational efficiency. The research methods include observation, interviews, and literature study, while the system development method uses the Waterfall model. The developed system features a dashboard, product data management, customer data, and transaction processing integrated in real-time. The results indicate that the system improves data accuracy, accelerates information processing, and facilitates stock and sales monitoring. Furthermore, the integration of customer data supports data-driven marketing strategies to enhance sales effectiveness. Therefore, the developed system serves as an effective solution to improve operational performance and service quality at Optik Husada.